HOW MUCH DO LEADERS SEEK TO BE INFLUENCED? THE CONCEPT OF SOCIAL INFLUENCE IN REVERSE IN REVERSE - Nowak, Andrzej; Zabłocka, Agata; Praszkier, Ryszard (Journal of Positive Management, 2018)
Purpose: Traditionally, the effects of social influence have been delineated in terms of “leaders” exerting influence over “followers.” Here we propose a new concept of social influence in which the leaders are influenced and, in fact, actively seek out that influence and build personal support networks that generate that influence. Approach: To examine the concept, we conducted both pilot (N=42) and main studies (N=113).The pilot study showed that leaders organize diverse support networks based on three major traits of the influence-givers: their competence, moral standards and creativity. Findings: The research confirmed that leaders cultivate five types of individual support networks or influence-providers: family and close friends, professional connections, colleagues and peers (mostly relating to leisure and entertainment), social engagement, and a local/neighborhood network. The research revealed several dependencies between the subjects’ occupation and their expectations from the influence-providers. We also documented that leaders seek basically two kinds of individual support: support from individuals from whom they expect low-order processed information, i.e., facts and data; (type A), and support from individuals from whom they expect high-order, processed information, i.e., opinions, advice, strategies and predictions; (type B). It also confirmed that selection of type A supporters is primarily based on competencies and type B supporters are typically selected based on moral standing and creativity. Implications: This article will empower leaders to better understand the value of their support networks, also to organize the flow of received information. Value/Originality: We are presenting an original concept of social influence in reverse, broadening the cognition of social influence in positive management.